Awareness and attitudes of undergraduate students towards plagiarism: are there any differences between genders? / Tuan Sarifah Aini Syed Ahmad ... [et al.] - Syed Ahmad, Tuan Sarifah Aini; Zainal Abedin, Nur Fadhlina; Ahmad, Irma; Paramasivam, Sheela; Wan Mustapha, Wan Zumusni (Universiti Teknologi MARA, 2022)
Plagiarism has become more prevalent in higher learning institutions. Tertiary students have the tendency to commit plagiarism as a quick solution for completing their assignments, or they may unintentionally commit it because they lack awareness towards it. Curbing plagiarism amongst tertiary students is important to maintain academic integrity. Thus, the study aimed to investigate whether there were any differences between genders on awareness and attitudes towards plagiarism amongst tertiary students. The study employed a quantitative method by using a set of questionnaires as the instrument to gather the data which was distributed via the class WhatsApp groups. The sample consisted of 50 undergraduate students from Universiti Teknologi MARA Cawangan Negeri Sembilan, Kampus Seremban, Malaysia, who were obtained through purposive sampling. The data collected were analysed by using the Statistical Packages for Social Sciences (SPSS). The results of the independent t-test demonstrated that there were no significant differences between genders on awareness and attitudes towards plagiarism. The results were also consistent when the Mann Whitney U tests were conducted. Therefore, the results suggest that being aware of plagiarism and attitudes towards plagiarism cannot be associated with gender. Consequently, higher learning institutions should educate all students regardless of gender to prevent plagiarism from occurring.